Relación entre las características de crecimiento y la composición bromatológica de los pastos Maralfalfa (Pennisetum spp) y Cuba OM-22 (Pennisetum purpureum x Pennisetum glaucum) en la estación experimental El Padmi de la Universidad Nacional de Loja - Cabrera Salinas, Celso David (2023)
Knowledge of the agronomic characteristics and nutritional value of pastures constitutes aspects of great importance for the proper management of pastures. The present research is oriented to the study of the relationships between the growth characteristics and the bromatological composition of the Maralfalfa (Pennisetum spp) and Cuba OM-22 (Pennisetum purpureum x Pennisetum glaucum) grasses in the edaphoclimatic conditions of the southern Ecuadorian Amazon. For this purpose, data generated in crops previously established at the “El Padmi” experimental station of the National University of Loja were used; With the help of the INFOSTAT statistical program (Version 2021), the corresponding correlation matrices were generated and prediction models were developed for the variables under study. The evaluation analysis demonstrated that the agronomic characteristics and nutritional value of Cuba OM-22 and Maralfalfa pastures are strongly related; Thus, between the cutting age, plant height, stem weight, leaf weight, plant weight, dry matter content, neutral detergent fiber (NDF), acid detergent fiber (ADF) and Lignin, a direct or positive evaluation of moderate to high is calculated, with coefficients greater than 0.6; Meanwhile, with the ash and crude protein (CP) content a negative or inverse compensation will be achieved with values greater than -0.8. The regression analysis presented a highly significant linear trend, which allowed the development of prediction models of the growth indicators and nutritional value of these species, in the edaphoclimatic conditions of the southern Ecuadorian Amazon. It is concluded that cutting age has a direct influence on growth characteristics and nutritional value, constituting an important tool to improve the management and use of pastures and forages in this region.